Accurate Calculation of the Maximum Grinding Wheel Diameter for the Form Grinding of Modification Herringbone Gears - Xunmin Yin; Haitao Jia; Runbo Zhang (Jixie chuandong)
An accurate calculation method of the maximum grinding wheel diameter for the form grinding of modification herringbone gears is proposed. A modified surface with three-section parabolic tooth profile is established. According to the meshing equation of the grinding wheel and the workpiece，the contact line equation of the grinding wheel is derived. The contact line of the grinding wheel is moved spirally around the axis of the workpiece，and considering the change of the center distance of the grinding wheel，a double modification of the herringbone gear is realized. According to the geometric conditions，when the grinding wheel is grinding the end point of the tooth surface，the maximum diameter of the grinding wheel is calculated，and the influence of the basic parameters，modification parameters and process parameters of the gear on the maximum diameter of the grinding wheel is analyzed. Numerical example simulation shows that tooth surface modification has little effect on the maximum diameter of the grinding wheel，and grinding depths have a greater influence on the maximum diameter of the grinding wheel. Both the number of teeth and the helix angle have an obvious effect on the maximum diameter of the grinding wheel.